Kelompok Dukungan Sebaya: Media Efektif Pencegahan HIV Pada Remaja - Tati Sumiati; Tutik Lestari; Muhammad Rivai; Suryadi M Ali; Israini Suriati; Muhammad Purqan Nur (Universitas Alifah Padang, 2025)
Peer support groups are an effective strategy in increasing knowledge, attitudes, and awareness of HIV prevention among adolescents. Health messages conveyed between adolescents are more easily accepted because they have strong social relationships and trust with each other. This activity aims to implement effective communication in peer support groups so that they can become pioneers of healthy behavior in the school environment. The implementation of this activity is a collaboration with the KPA Ternate City, the location of the activity at SMP Negeri 6 Ternate City on Friday, December 5, 2025. The method used was role-playing and discussion. Participants were representatives of junior high school students in Ternate City, the number of participants was 42 people consisting of 76.2% female, the largest age was 14 years (45.2%), the youngest age was 12 years and the oldest age was 15 years. All were 7th grade students. The results of the role-playing activity showed that 4 groups were able to practice the role of peer agents, formulating mini-dramas based on predetermined themes. Based on the mini drama script and discussion, it was seen that participants were able to explain the impact of HIV on adolescents, issues of healthy interpersonal relationships including issues of stigma and discrimination, healthy communication about sexuality and relationships, and the role of adolescents as peer educators.